ЕPILEPTIC SEIZURES IN PATIENTS WITH CRANIOVERTEBRAL JUNCION ANOMALY - M. R. Yarmuchametova (Эпилепсия и пароксизмальные состояния)
Purpose: Studing seizure in patients with Chiari I malformation. Methods: 111 patients (58 females, 53 males) with Arnold-Chiari I malformation and epilepsy were examined with cognitive and behavioral examinations, EEG, MRI. Results: Patients with Arnold-Chiari I malformation have been next forms epilepsy: symptomatic epilepsy – 53,9%, cryptogenic epilepsy – 43,4%, juvenile мyoclonic epilepsy – 0,9%, juvenile absence epilepsy – 1,8%. The neurological symptoms were: cranial nerve dysfunction – 27%, the pyramidal symptoms – 12,6%, cerebellar symptoms – 0,9% and 59,5% patients have not neurological signs. The radiological features are: association of small posterior cranial fossa volume and Arnold-Chiari I malformation – 6%, association basilar impression and Arnold-Chiari I malformation with small posterior cranial fossa volume – 2%, basilar impression and Arnold-Chiari I malformation – 1%. Conclusion. The Arnold-Chiari I malformation, basilar impression and small posterior cranial fossa volume are anatomic finds in the MRI examinations in patients with epilepsy.